DIE DIENS VAN DIE GELOWIGE IN DIE LUKAS-GESKRIFTE - De Villiers, Pieter G. R. (Scriptura, 1982)
Service of the believer according to Luke’s writings The service of the believer in this world, as seen by New Testament writers, should be interpreted as it is carefully depicted by every writer, according to the situation and frame of reference of his readers, and the community in which they live. This is a necessary first step towards finding answers to important ethical questions such as how New Testament ethics could be relevant to modern society - so completely different from the Hellenistic and Palestinian societies. The article investigates Luke’s understanding of the believer’s service and its unique nature. Luke interprets the person of Jesus, inter alia in an analgous, but also antithetical way against the model or background of the endangered Benefactor, which according to various documents, was an established title and concept in the Hellenistic era. It is noteworthy that Luke is the only Evangelist who employs this title. An analysis of the finely structured Luke 6:26-36 and a comparison with the parallel parts in Matthew illustrates beyond doubt that Luke employed this concept further to illuminate and stress the importance and nature of the relationship with God as Benefactor. In Luke 22:15ff Luke’s profound Christological and ethical concept both of which are influenced by the Benefactor-model, are joined in a subtle and striking manner. Luke’s concept of service implies that a person is a believer because, and only as, he serves. This service has a spiritual, but also a thorough-going concrete nature; it seeks no reward, it is humble (because it concerns God!) and it is a joyful experience.